PENGARUH MOTIVASI KERJA, DISIPLIN KERJA, DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN HOTEL PURI KHATULISTIWA BANDUNG - Ridma Meltareza; Agam Dwi Permana (JURNAL PARIWISATA VOKASI, 2022)
The role of human resource management can look good if the company strives for employees to have a positive impact on the company and have productive performance. Puri Khatulistiwa hotel, 2019-2021 experienced a decline that was influenced by several variables in employee performance levels. The method used in this research is a quantitative method with a descriptive. Sampling by taking the entire population of 40 people or census techniques. Data analysis techniques used descriptive analysis tests, classic assumption tests consisting of normality tests, heteroscedasticity tests, multicollinearity tests, linearity tests, multiple linear regression analysis, multiple correlation analysis, and the coefficient of determination. The results showed that the descriptive analysis stated that Employee Performance was in a Good category, Work Motivation was in the Enough category, Work Discipline was in the Enough category, and Physical Work Environment was in the Fairly Comfortable category.